(untitled) (Economic Journal of Development Issues, 2012)
The main objective of this study is to find the economic impact of community forestry. Specifically the study aims to indentify the elements of cost and benefits of community forestry and estimate the monetary value of costs and benefits. This study is basically based on secondary information including unpublished documents of Nepal Swiss Community Forestry Project (NSCFP). Due to the lack of refined data on the benefits and costs, first elements of costs and benefits were identified and estimation of monetary benefits and costs has been estimated with certain assumptions. The study found that annual cost for the management of community forestry is about NRs. 119 thousand for each community forest user’s group in the studied three districts. Of the total costs, about 64% is borne by the forest user’s group households mostly in the form of labour. The donor contributed about 16% and the Government of Nepal contributed about 13 % of the total costs.Similarly the annual monetary benefits (only direct) per Community Forest User Group (CFUG) per year is NRs. 710 thousand. This indicates that the benefits are about 7 times greater than the costs even without considering the indirect benefits. Of the total about 80% benefit comes from the forest products, about 11% from time saving and about 7% from employment generation due to better management of community forestry. It is also found that CFUGs are able to mobilize about NRs. 38 million and utililizing part of it for the development of community in different ways. DOI: http://dx.doi.org/10.3126/ejdi.v13i0.7212 Economic Journal of Development Issues Vol.13 & 14 2011, pp.75-96